Quasi-biweekly oscillation in sea level along the western Bay of Bengal. (1st December 2021) - Anup, N.; Vijith, V.; Jithin, A.K.; Rohith, B.; Amol, P.; Francis, P.A.
Abstract: This study investigates the variability and sources of Quasi-Biweekly (QB) oscillation (10–20 days) in coastal sea level along the western boundary of the Bay of Bengal (BoB) using tide-gauge data and simulations from a very high-resolution regional model. Observations show most significant spectral energy in the QB band ( ∼ 12 days) exists in the northernmost location (Paradeep) with an amplitude of about 5–10 cm in sea level and energy in this band decreases equatorward along the coast. The QB oscillations in sea level contribute up to 16%–36% of the total subtidal sea-level variability in the western BoB and these oscillations are more pronounced during June–November. It is observed that sea-level oscillations in the QB band propagate equatorward along the east coast of India as coastal-trapped waves with a phase speed of about 2–4 ms −1 and this speed is consistent with the theoretical estimates. Our study revealed that the strong QB winds found in the northern BoB are one of the forcing factors that excite QB oscillation in sea level in the western BoB. Further analysis using numerical simulations shows that the QB sea level propagating from the equatorial Indian Ocean and QB oscillation generated by strong winds associated with the tropical cyclones formed in the BoB also contribute to QB coastal sea-level fluctuations in this region. Graphical abstract: Highlights: We study the quasi-biweekly (QB) oscillations in sea level along the western Bay of Bengal. QB oscillations contribute 16%–36% of the total subtidal sea-level variability. QB sea-level oscillations propagate equatorward as a coastal-trapped wave (CTW). Strong QB winds in the head of the Bay of Bengal can excite CTW in the QB band. CTW in QB band originating from the equator and tropical cyclones also contribute.